Association between non-invasive liver fibrosis scores and occurrence of health adverse outcomes in older people. Issue 9 (September 2019) - De Vincentis, Antonio; Costanzo, Luisa; Vespasiani-Gentilucci, Umberto; Picardi, Antonio; Bandinelli, Stefania; Ferrucci, Luigi; Antonelli Incalzi, Raffaele; Pedone, Claudio
Abstract: Background: The relation between liver fibrosis scores and health outcomes in older people has been barely investigated. We aimed to evaluate the association of four liver fibrosis scores (fibrosis-4 -FIB-4-, NAFLD fibrosis score -NFS-, BARD and aspartate aminotransferase/alanine aminotransferase ratio -AST/ALT-) with mortality and incident disability at 6 years in an older population. Methods: We studied 962 individuals aged ≥65 (mean age 74.4; female 55.5%) with a mean follow-up of 95.7 months, enrolled in the InCHIANTI study. The relationship between liver fibrosis scores and mortality and disability was assessed through Cox and log-binomial regressions. Results: NFS and FIB-4 were associated with higher overall (aHR ranging 1.38–1.78 for intermediate risk of fibrosis and 1.60–2.02 for high risk) and cardiovascular (aHR ranging 1.76–2.90 for intermediate and 2.22–2.42 for high risk) mortality. AST/ALT and BARD were only associated with overall mortality. Only NFS and FIB-4 high risk classes were associated with incident disability (aRR ranging 1.93–2.76). Despite poor sensitivity, all scores showed high specificity (ranging 0.88–0.95). Conclusion: Higher risk of liver fibrosis is associated with higher risk of poor health outcomes. Liver fibrosis scores may help to stratify the risk and, mainly, identify elderly patients with favorable prognosis.